Optimization of Fermentation Medium for the Production of Glucose Isomerase Using Streptomyces sp. SB-P1. (26th July 2012) - Bhasin, Sheetal; Modi, H. A.
Abstract : The combination of medium ingredients has a profound influence on the metabolic pathways running in the microorganism which regulates the production of numerous metabolites. Glucose isomerase (GI), an enzyme with huge potential in the market, can isomerise glucose into fructose. GI is used widely for the production of High-Fructose Corn Syrup (HFCS). HFCS is used as a sweetener in food and pharmaceutical industries. Streptomyces are well-known producers of numerous enzymes including glucose isomerase. An array of 75 isolates was screened for the production of glucose isomerase. The isolate Streptomyces sp. SB-P1 was found to produce maximum amount of extracellular GI. Sucrose and raffinose among pure carbon sources and corn cob and wheat husk among crude agro residues were found to yield high enzyme titers. Potassium nitrate among pure nitrogen sources and soy residues among crude sources gave maximum production. Quantitative effect of carbon, nitrogen, and inducer on GI was also determined. Plackett-Burman design was used to study the effect of different medium ingredients. Sucrose and xylose as carbon sources and peptone and soy residues as nitrogen sources proved to be beneficial for GI production.